The Impact of Aggregators on Internet News Consumption - Athey, Susan,Mobius, Markus,Pal, Jeno (National Bureau of Economic Research, 2021)
A policy debate centers around the question how news aggregators such as Google News affect traffic to online news sites. Many publishers view aggregators as substitutes for traditional news consumption while aggregators view themselves as complements because they make news discovery easier. We use Spain as a natural experiment because Google News shut down altogether in response to a copyright reform enacted in December 2014. We compare the news consumption of a large number of Google News users with a synthetic control group of similar non-Google News users. We find that the shutdown of Google News reduces overall news consumption by about 20% for treatment users, and reduces page views on publishers other than Google News by 10%. This decrease is concentrated around small publishers. We further find that users are able to replace some but not all of the types of news they previously read. Post-shutdown, they read less breaking news, hard news, and news that is not well covered on their favorite news publishers. These news categories explain most of the overall reduction in news consumption, and shed light on the mechanisms through which aggregators interact with traditional publishers
10.3386/w28746
Keywords: Arbeitspapier; Graue Literatur; Mediale Berichterstattung; Digitale Dienste; Konsumentenverhalten; Internetnutzung; Digitale Plattform; Urheberrecht; Spanien; Google News